Book-Tax Conformity Level on the Relationship between Tax Reporting Aggressiveness and Financial Reporting Aggressiveness - Nurul Aisyah Rachmawati; Dwi Martani (Australasian Accounting, Business and Finance Journal, 2017)
The purpose of this study is to examine the effect of book-tax conformity level on the relationship between tax reporting aggressiveness and financial reporting aggressiveness. Different from Frank et al. (2009) and Lennox et al. (2013), this study considers endogeneity problem to minimize biased results. Using the companies listed on the Indonesia Stock Exchange for 2013-2016, this study found that there is endogeneity problem in the relationship between tax reporting aggressiveness and financial reporting aggressiveness, but no causality relationship. In this case, only tax reporting aggressiveness that affects financial reporting aggressiveness, but not otherwise. Consistent with the hypothesis, this study also found that firm with a low level of BTC is more weakened trade-offs between tax reporting aggressiveness and financial reporting aggressiveness than firm with high level of BTC. These results are consistent either with or without include the industry dummy.
Keywords: book-tax conformity; tax reporting aggressiveness; financial reporting aggressiveness; Indonesia.